The Pittsburgh Fatigability Scale for Older Adults: Development and Validation - Glynn, Nancy W.; Santanasto, Adam J.; Simonsick, Eleanor M.; Boudreau, Robert M.; Beach, Scott R.; Schulz, Richard; Newman, Anne B. (Journal of the American Geriatrics Society (JAGS), 2015)
Objectives To describe the development of the Pittsburgh Fatigability Scale (PFS) and establish its reliability and concurrent and convergent validity against performance measures. Design Cross‐sectional. Setting University of Pittsburgh, Pittsburgh, Pennsylvania. Participants Scale development sample: 1,013 individuals aged 60 and older from two registries; validation sample: 483 adults aged 60 and older from the Baltimore Longitudinal Study of Aging (BLSA). Measurements The scale development sample and BLSA participants self‐administered an initial 26‐item perceived fatigability scale. BLSA participants also completed measures of performance fatigability (perceived exertion from a standard treadmill task and performance deterioration from a fast‐paced long‐distance corridor walk), a 6‐m usual‐paced corridor walk, and five timed chair stands. Results Principal components analysis with varimax rotation reduced the 26‐item scale to the 10‐item PFS. The PFS showed strong internal consistency (Cronbach's alpha 0.88) and excellent test–retest reliability (intraclass correlation 0.86). In the validation sample, PFS scores, adjusted for age, sex, and race, were greater for those with high performance fatigability, slow gait speed, worse physical function, and lower fitness, with differences between high and low fatigability ranging from 3.2 to 5.1 points (P < .001). Conclusion The 10‐item PFS physical fatigability score is a valid and reliable measure of perceived fatigability in older adults and can serve as an adjunct to performance‐based fatigability measures for identifying older adults at risk of mobility limitation in clinical and research settings.